Surface orientation dependence of irradiation-induced hardening in a polycrystalline zirconium alloy. (15th March 2019) - Yang, H.L.; Kano, S.; McGrady, J.; Shen, J.J.; Matsukawa, Y.; Chen, D.Y.; Murakami, K.; Abe, H.
Abstract: A combination of ion-accelerator irradiation, nanoindentation tests, and electron backscatter diffraction analysis was utilized to probe the crystal orientation dependence of irradiation-induced hardening in a Zr alloy. The nanohardness at the [0001] orientation exhibited the highest value, which gradually decreased when the orientation deviated from the [0001] axis to the [ 10 1 ¯ 0 ] and 2 1 ¯ 1 ¯ 0 axes, regardless of the irradiation dose. Crystal-orientation-dependent irradiation-induced hardening is further confirmed. The lowest hardening was observed at [0001] orientation, and the hardening effect intensified toward the [ 10 1 ¯ 0 ] and [ 2 1 ¯ 1 ¯ 0 ] orientations, reaching the maximum at a rotation angle of ~55° with respect to [0001]. Graphical abstract: Unlabelled Image